Pelatihan Public Speaking dan Focus Group Discussion - Menuju Kepemimpinan yang Inspiratif dalam Berorganisasi di SMA Islam 1 Sleman - Nabila Putri Nawati; Putri Isnu Marthania; Moni Sulistiyawati; Yuliami Anggi Saputri; Anjessa Putra; M. Alfian Dwi Cahya; Popi Andiyansari (Jurnal ABDI RAKYAT, 2025)
Public speaking training is a very important skill in the world of organizations, especially for students who are members of OSIS. The activity "Public Speaking Training for FGD Towards Inspirational Leadership in Organizations" was held at SMA Islam 1 Sleman with the aim of improving public speaking and student leadership skills through the Focus Group Discussion (FGD) method. The methods used in this training include the delivery of materials by people who are experts in communication, group discussion sessions, and public speaking practice training. Evaluation of the success of the training was carried out through pre-tests and post-tests, which showed an increase in participants' understanding of public speaking and leadership. The results of this training showed that the FGD method was effective in building self-confidence, improving communication skills, and encouraging students to become more inspiring leaders.